Implementasi Pengukuran Indeks Kepuasan Masyarakat sebagai Instrumen Optimalisasi Layanan di Rumah Sakit - Handayani, Susi; Endah Saptutyningsih; Diah Setyawati Dewanti (Universitas Muhammadiyah Pontianak, 2026)
This study analyzes the Public Satisfaction Index (PSI) as a strategic instrument for service optimization at RS PKU Muhammadiyah Mayong based on 2025 survey data. Using descriptive quantitative methods, nine service elements were evaluated per PERMENPAN-RB 14/2017. Results show an average PSI score of 82.09 (Good). While cost and infrastructure perform excellently, service speed and complaint handling require acceleration. ICU recorded the highest satisfaction (87.31), whereas the Outpatient Clinic was lowest (78.66). Recommendations focus on registration digitalization, hospitality competence, and integrated complaint management. Periodic PSI measurement provides an empirical foundation for evidence-based policy to maintain patient loyalty and sustainable healthcare quality.